Receiving maternity care during the COVID-19 pandemic: Experiences of women's partners and support persons - Vasilevski, V.; Sweet, L.; Bradfield, Zoe; Wilson, A.N.; Hauck, Yvonne; Kuliukas, Lesley; Homer, C.S.E.; Szabo, R.A.; Wynter, K. (ELSEVIER, 2022)
Background: In Australia, the provision of maternity care during the COVID-19 pandemic was significantly altered to limit transmission of the virus. Many hospitals limited face-to-face appointments to only the pregnant woman and restricted the number of support people present during labour, birth, and postnatal visits to one person. How these restrictions were experienced by partners and support persons of childbearing women are unknown. Aim: To explore the experiences of partners and support persons of women receiving maternity care during the COVID-19 pandemic. Methods: A two-phased qualitative study including an online survey and interviews. Analysis was undertaken using content analysis. Findings: Partners and support persons experienced a sense of ‘missing out’ from the pregnancy and maternity care experience because of changes in the provision of care during the pandemic. They reported feelings of isolation, psychological distress, and reduced bonding time with babies. Conflicting information and processes within and across maternity services contributed to feelings of uncertainty and a perceived reduction in the quality of care. Partners and support persons were negatively impacted by restrictions on maternity wards, however they also perceived these to be of benefit to women. Discussion: Many partners and support persons were negatively impacted by restrictions in maternity services during the pandemic; strategies to ensure their active involvement in maternity care are needed. Conclusion: This study offers insights from the unique perspective of partners and support people of women receiving maternity care during the pandemic. Policies and processes that exclude partners and support persons need to be reconsidered.